Penerapan Goal Setting Untuk Meningkatkan Motivasi Belajar Siswa : Implementation of Goal Setting to Increase Student Learning Motivation - Moh Samsudin Febri Anto; Dra. Dwi Nastiti, M.Si (Academia Open, 2025)
General Background: Learning motivation plays a central role in determining students’ academic engagement and achievement within formal education systems. Specific Background: Empirical findings indicate that many secondary school students demonstrate low levels of learning motivation, requiring structured psychological and educational interventions. Knowledge Gap: Although goal setting has been widely discussed in motivational theory, limited experimental evidence has examined structured goal setting training programs implemented directly in classroom settings. Aims: This study aims to examine differences in students’ learning motivation before and after participation in a goal setting training program. Results: Using an experimental approach with pretest and posttest measurement, statistical analysis revealed a significant increase in learning motivation scores following the training intervention, indicating measurable changes in students’ motivational levels. Novelty: The study provides empirical evidence from a structured training design applied in a secondary school context, integrating goal setting principles with practical classroom implementation. Implications: The findings support the integration of systematic goal setting training into educational practice as a structured motivational strategy and provide empirical reference for future research in educational psychology and student self-regulation.Keywords: Goal Setting Training, Learning Motivation, Experimental Study, Secondary School Students, Educational Psychology Key Findings Highlights: Post-intervention measurements showed statistically significant score improvement. Structured training sessions demonstrated measurable motivational change. Classroom-based implementation confirmed practical feasibility of the program.